Identification of Aptamers that Specifically Bind to A1 Antigen by Performing Cell-on Human Erythrocytes: - Hosseini, Seyed Mohammad Hasan; Bassami, Mohammad Reza; Haghparast, Alireza; Sankian, Mojtaba; Hashemi Tabar, Gholamreza (Galen Medical Journal, 2020)
Background: The apply of aptamers as a new generation’s way to probe diagnostic for the detection of target molecules has gained ground. Aptamers can be used as alternatives to diagnostic antibodies for detection of blood groups due to their unique features. This study was aimed to produce DNA diagnostic aptamer detecting the antigen of A1 blood group using the Cell-Selex method. Materials and Methods: DNA aptamer was isolated against A1 RBC antigen after ten stages of Cell-Selex and amplification by an asymmetric polymerase chain reaction. The progress of the stages of selection was evaluated using flow cytometry analysis, which the DNA aptamer isolated from the tenth cycle with an affinity of 70% fluorescent intensity, was selected from four positive colonies followed by determination of the sequences and secondary structures. Results: The aptameric sequence obtained from C4 cloning was calculated with the highest binding affinity to A1 antigen having an apparent dissociation constant (Kd value) of at least 29.5 ± 4.3 Pmol, which was introduced as the selected aptamer-based on ΔG obtained from a colony of C4 equal to –13.13. Conclusion: The aptamer obtained from using Cell-Selex method could be used as an example for the development of diagnostic tools such as biosensors for detecting A1 blood group antigens. [GMJ.2020;9:e1657]